Findlay-Grubert versus Rybczynski : Testing Growth Hypotheses in Classic Trade Theories Using Singapore's Industries - Kee, Hiau Looi (2012)
In the classic literature of multi-sector small open economy, there are two, competing hypotheses on growth. Findlay and Grubert (1959) showed that productivity growth in one sector affects the factor intensity of all sectors. Rybczynski (1955) presents the long run growth effects of endowment accumulations. Focusing on the most open small economy, this paper tests the two hypotheses directly by estimating the relative contributions at the industry level for Singapore. Results suggest that productivity contributes more in the electronics industry, but domestic endowments matter more in other industries. This paper is also the first to present evidence on the Findlay-Grubert effect by showing that the productivity growth of the electronics industry pushes up the capital-labor ratios of all industries.